Syntactic-semantic classes and origin of compounds in the Aukštaitian dialect of the Klaipėda region - Stundžia, Bonifacas (Baltistica, 2022)
The article analyses the syntactic-semantic classes and origin of 124 compounds (mostly substantives) recorded in the Aukštaitian dialect of the Klaipėda region (abbreviated as KlpA). The main attention is given to the compounds which are characteristic of the researched dialect, including the neighbouring areas of Western and Southern Žemaitian as well as Western Aukštaitian dialects. The research material was collected from audio recordings (ca. 29 hours of duration) available at the Institute of the Lithuanian Language (see KlpAĮr) as well as from the published texts of the dialect in question (see LKT, KlpAT, LKTCh, VAK & KlpA). The author of this article also collected compounds from the published texts of the Northern Žemaitian dialect (see KrtnT, SkdT, TrkT and ŽemDzT) as well as from the manuscript texts of the South Western Aukštaitian dialect (see PVAT) in order to evaluate the status of compounding in a broader western area of Lithuanian dialects.The analysis leads to the following conclusions. Firstly, compounding seems to be a rare phenomenon compared to derivation in the whole western area of Lithuanian dialects. Secondly, determinative compounds comprise more than half of all the collected KlpA compounds. The said class of compounds is the most productive in the western area of Lithuanian dialects as well as in the Baltic and Germanic languages. As to the productivity of both possessive and verbal governing compounds, a variation is observed in different dialects, and this phenomenon may at least in part be predetermined by the themes of the texts as well as by the education of the informants. Thirdly, compounds which are peculiar to the dialect of KlpA and its surrounding area comprise less than one fifth of the analysed formations (see examples 1–5, 10, 11, 14–18, 35–40, 63–67). Many of the said compounds are morpheme-to-morpheme calques from German, particularly in the case of formations with at least one borrowed member (the interrelation between structural and material borrowing is also characteristic of compounds registered in the 17th–18th c. manuscript dictionaries of Lithuania Minor, see Stundžia 2020, 77ff.). About half of the compounds have entered the dialects from public usage. Such areal-etymological diversity of the analysed formations is predetermined mostly by the erudition of the informants. For many of them the native language is German, and besides Lithuanian, they also know Russian, and a few of them know Polish.
Keywords: Lithuanian dialects; syntactic-semantic classes of compounds; determinative compounds; possessive compounds; verbal governing compounds; compound calques